Immunotherapy versus targeted therapy in management of recurrent squamous cell carcinoma of oral tongue - Nadimul Hoda; Aastha Moza; K.P. Amith; K.S. Sabitha (Oral Oncology Reports)
Background: Targeted therapies, and more recently immunotherapy, have dramatically changed the landscape of treatments in oral cavity cancers and improved clinical outcomes. The benefit from targeted therapy and immune checkpoint inhibitors is however tampered by toxicities that affect different sites, including the oral cavity. Agents frequently reported to be associated with oral complications include tyrosine kinase inhibitors (TKIs), inhibitors of the VEGF receptor (VEGFR), anti-epidermal growth factor receptor (anti-EGFR), vascular endothelial growth factor (VEGF), mammalian target of rapamycin inhibitors (mTORis), and, more recently, immune checkpoint inhibitors (ICIs). Herein, our review talks about the comparison of immunotherapy and targeted therapy being the newer advances and its relevance for oral tongue carcinomas. Method: ology: A sample size pertaining to 14 relevant articles on immunotherapy and targeted therapy were chosen to combat squamous cell carcinoma of oral tongue. The primary and secondary parameters were overall survival and recurrence rate. Results: The basis of our statistical analysis were 14 articles selected wherein immunotherapy and targeted therapy was chosen. An overall recurrence rate of 4.0 % ± 0.1 % and overall survival rate of 75.3 % ± 11.4 % was substantiated. Our analysis consisted of both the forms of therapies where in immunotherapy precedes targeted therapy in terms of confirmed clinical trials. Conclusion: This newer modality of the cancer treatment forms the fourth pillar supporting surgery, chemotherapy, and radiotherapy. Therefore careful selection of patient is the key for success rate of immunotherapy, which is based on patient's immunological contexture. Based on the targeted drug delivery systems with specific physiochemical properties and tailored structure, carriers can load anti-cancer drugs to target the malignant cells.